RECLAIMING RUINS: AN ECOFEMINIST ANALYSIS OF PRASHANTH SRIVATSA’S A GIRL AT THE END OF THE WORLD - Ramadhani, Nadia; Purwarno, Purwarno (SIGEH ELT : Journal of Literature and Linguistics, 2026)
Environmental degradation and gender oppression have been widely theorized as interconnected within ecofeminist discourse; however, existing scholarship has largely focused on canonical and large-scale dystopian narratives, leaving contemporary short fiction that explores these dynamics in intimate, post-apocalyptic contexts underexamined. Addressing this gap, this study analyzes how intersecting systems of ecological crisis and patriarchal domination are represented in A Girl at the End of the World by Prashanth Srivatsa. Drawing on the ecofeminist frameworks of Vandana Shiva and Val Plumwood, the research examines how the narrative critiques anthropocentric and patriarchal logics while reimagining ecological restoration.Using a qualitative descriptive design grounded in ecofeminist literary criticism, the study employs document analysis, thematic coding, and interpretive textual analysis to identify key ecofeminist patterns within the text. The findings reveal six central categories—domination, othering, ruin, ecological trauma, care ethics, and reclamation—that structure the narrative’s representation of the relationship between women and nature. The analysis further demonstrates that the female protagonist operates as a symbolic mediator of ecological renewal, transforming post-apocalyptic ruins into spaces of resistance, ethical care, and environmental regeneration.These findings underscore how contemporary dystopian fiction mobilizes localized, post-apocalyptic settings to reconfigure gender–nature interdependence and challenge hierarchical human–nature relations. By integrating ecofeminist theory with close textual analysis, this study contributes to gender- and environment-oriented literary criticism while extending ecofeminist inquiry into contemporary speculative fiction and discussions of ecological justice.